2005
DOI: 10.1017/s0954579405050388
|View full text |Cite
|
Sign up to set email alerts
|

Attention-deficit disorder (attention-deficit/ hyperactivity disorder without hyperactivity): A neurobiologically and behaviorally distinct disorder from attention-deficit/hyperactivity disorder (with hyperactivity)

Abstract: Most studies of attention-deficit/hyperactivity disorder (ADHD) have focused on the combined type and emphasized a core problem in response inhibition. It is proposed here that the core problem in the truly inattentive type of ADHD (not simply the subthreshold combined type) is in working memory. It is further proposed that laboratory measures, such as complex-span and dual-task dichotic listening tasks, can detect this. Children with the truly inattentive type of ADHD, rather than being distractible, may inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
292
2
35

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 352 publications
(351 citation statements)
references
References 171 publications
22
292
2
35
Order By: Relevance
“…Consistent with this, drugs used to treat ADHD, including psychostimulants, SNRIs and a 2 -receptor agonists, improve an array of PFCdependent processes (Chamberlain et al, 2007;Diamond, 2005;Mehta et al, 2001;Turner et al, 2005). Neurochemically, low and clinically relevant doses of MPH preferentially increase extracellular levels of NE and DA within the PFC relative to other cortical and subcortical regions (for review, Berridge and Devilbiss, 2011).…”
Section: The Pharmacology Of Adhd: Preferential Targeting Of the Pfcmentioning
confidence: 96%
“…Consistent with this, drugs used to treat ADHD, including psychostimulants, SNRIs and a 2 -receptor agonists, improve an array of PFCdependent processes (Chamberlain et al, 2007;Diamond, 2005;Mehta et al, 2001;Turner et al, 2005). Neurochemically, low and clinically relevant doses of MPH preferentially increase extracellular levels of NE and DA within the PFC relative to other cortical and subcortical regions (for review, Berridge and Devilbiss, 2011).…”
Section: The Pharmacology Of Adhd: Preferential Targeting Of the Pfcmentioning
confidence: 96%
“…Nevertheless, it is clear that ADHD is not a unitary disorder Nigg and Casey, 2005;Diamond, 2005), and other behavioral symptoms of ADHD are not easily explained by the reduced DA hypothesis. For example, ADHD participants typically show more withinsubject variability in their reaction times (Leth-Steensen et al, 2000;Lijffijt et al, 2005;Castellanos et al, 2005).…”
Section: Noradrenaline Dysfunction In Adhdmentioning
confidence: 99%
“…[5][6][7][8] However, major difficulties appear in tasks that require sustained attention, or attentional control and redirection of attention. 5,8,9,12 Most studies with groups of children, adolescents, and adults with ADHD which used the RSVP paradigm have shown that these participants exhibit a powerful AB effect as compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 However, they usually exhibit difficulties in voluntary processes, such as redirecting attention to new stimuli, sustaining their attentional level or, in some tasks, with persevering. [5][6][7][8] Many studies have investigated selective visual attention (i.e., the ability to focus on relevant stimuli while ignoring irrelevant distractors) in children, adolescents, and adults with ADHD. Some of this research indicates that, although ADHD children may be distracted by irrelevant stimuli, they are no more affected than are controls.…”
Section: Introductionmentioning
confidence: 99%